2013
DOI: 10.3109/2000656x.2013.787085
|View full text |Cite
|
Sign up to set email alerts
|

Use of intraoperative indocyanin-green angiography to minimize wound healing complications in abdominal wall reconstruction

Abstract: Complication rates following abdominal wall reconstruction (AWR) remain high. Early complications are related to skin necrosis and delayed healing, whereas late complications are related to recurrence. When concomitant body contouring procedures are performed, complication rates can be further increased. It is hypothesised that fluorescent angiography using indocyanin green (ICG) can identify poorly perfused tissues and thus reduce the incidence of delayed healing. A retrospective review was conducted of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Patel et al [41] demonstrated reduced wound complications with ICG-FA in 5 patients. The authors have also provided the first guideline for the use of ICG-FA in this field: an absolute perfusion unit threshold of ten with a 5 mg dose of ICG with the SPY Elite Ò system.…”
Section: Discussionmentioning
confidence: 98%
“…Patel et al [41] demonstrated reduced wound complications with ICG-FA in 5 patients. The authors have also provided the first guideline for the use of ICG-FA in this field: an absolute perfusion unit threshold of ten with a 5 mg dose of ICG with the SPY Elite Ò system.…”
Section: Discussionmentioning
confidence: 98%
“…Combining an expertise in wound healing and soft-tissue management with mechanical concepts borrowed from experience with breast and hand surgery, plastic surgeons have been instrumental in the introduction and evaluation of new techniques and materials for abdominal wall reconstruction. 3,4,1218 However, although these advances have yielded improved surgical outcomes with regard to hernia repair, there has not been an equivalent improvement in the general surgeon’s ability to provide a reliable laparotomy closure. A recent review of outcomes from two large prospective trials reported an incisional hernia rate of 22.4 percent at 3 years, a rate comparable to that reported more than 30 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was extremely pleased with his cosmetic outcome and continues to report a much better quality of life after this operation ( Figure 5). ACT scan performed 6 months later showed an intact repair ( Figure 6) [1][2][3][4][5][6][7][8][9][10][11][12][13]. …”
Section: Case Presentationmentioning
confidence: 99%